Case Report: Recanalization of Branch Retinal Artery Occlusion Due to Microthrombi Following the First Dose of SARS-CoV-2 mRNA Vaccination - Kang, Min Seung; Kim, Sang Yoon; Kwon, Han Jo (Frontiers in Pharmacology, 2022)
Background: We report on a patient with a branch retinal artery occlusion (RAO) and its recanalization based on multimodal retinal and angiographic images after he was administered the first dose of the SARS-CoV-2 mRNA vaccine. Case summary: A 64-year-old man complained of a right, painless, inferior field defect 3 days after the first dose of BNT162b2 vaccination. Fundus examination revealed decolorization of the right upper macula, including microthrombi in the superior proximal branch of the retinal artery. Optical coherence tomography angiography revealed upper macular hypoperfusion. Fluorescein angiography revealed prolonged arteriovenous transit to the macula. After paracentesis with antiplatelet medications, the artery was recanalized as the thrombi dissolved, and the right visual field was recovered. Re-occlusion did not occur during the 3 months after the second mRNA vaccination. Conclusion: Non-embolic thrombotic RAO may develop shortly after the SARS-CoV-2 mRNA vaccine. Ophthalmologists should consider RAO as a possible post-vaccination adverse event. The temporal association between mRNA vaccination and RAO onset with evidence of microthrombi might provide additional clues to elucidate the unpredictive arterial thrombosis following SARS-CoV-2 mRNA vaccination.